1T phase as an efficient hole injection layer to TMDs transistors: a universal approach to achieve p-type contacts. (13th June 2018) - Hu, Xiaohui; Wang, Yifeng; Shen, Xiaodong; Krasheninnikov, Arkady V; Sun, Litao; Chen, Zhongfang
Abstract: Recently, the fabricated MoS2 field effect transistors (FETs) with 1T-MoS2 electrodes exhibit excellent performance with rather low contact resistance, as compared with those with metals deposited directly on 2H-MoS2 (Kappera et al 2014 Nat. Mater .13 1128), but the reason for that remains elusive. By means of density functional theory calculations, we investigated the carrier injection at the 1T/2H MoS2 interface and found that although the Schottky barrier height (SBH) values of 1T/2H MoS2 interfaces can be tuned by controlling the stacking patterns, the p-type SBH values of 1T/2H MoS2 interfaces with different stackings are lower than their corresponding n-type SBH values, which demonstrated that the metallic 1T phase can be used as an efficient hole injection layer for 2H-MoS2. In addition, as compared to the n-type Au/MoS2 and Pd/MoS2 contacts, the p-type SBH values of 1T/2H MoS2 interfaces are much lower, which stem from the efficient hole injection between 1T-MoS2 and 2H-MoS2 . This can explain the low contact resistance in the MoS2 FETs with 1T-MoS2 electrodes. Notably, the SBH values can be effectively modulated by an external electric field, and a significantly low p-type SBH value can be achieved under an appropriate electric field. We also demonstrated that this approach is also valid for WS2, WSe2 and MoSe2 systems, which indicates that the method can most likely be extended to other TMDs, and thus may open new promising avenues of contact engineering in these materials.